Distribution of the montane spruce forest on peat Bazzanio-Piceetum in the Beskid Mały Mts., its threats and protection - Brzustewicz, Małgorzata; Barć, Alicja (Biodiversity: Research and Conservation, 2006)
Studies on the distribution and differentiation of Bazzanio-Piceetum in the Beskid Mały Mts. started in 2003. Patches of the association were found in the managed State Forests of the Sucha and Jeleśnia Forest Inspectorates, as well as in private forests near Targoszów, Krzeszów and Tresna. Such a localisation is influenced by serious threats caused by forest management: deforestation of slopes, forest roads or trails which cross patches of vegetation and by wood transport along stream beds. These activities disturb the hydrological relationships in the area and become the cause of elimination of many hygrophilous species. Two subassociations: Bazzanio-Piceetum equisetetosum sylvaticae and B.-P. typicum were distinguished up to now, upon the analysis of phytosociological materials. The fitness of the phytocoenoses is evidenced by the abundance of many peat-moss and rare liverwort species, Bazzania trilobata among others, which are well-known indicators of changes in the natural environment. All patches of Bazzanio-Piceetum in the Beskid Mały Mts. are unique, both because of the role played by bryophytes in their phytocoenoses, and the combination of specific habitat conditions essential for their development. Their protection is an urgent need.